Analisis Kesalahan Berbahasa Tataran Sintaksis dalam Berita Haluanriau.co - Mardiah, Raihani; Hermaliza, Hermaliza (UIR Press, 2024)
Analysis od language errors at the Syntactic level is a branch of linguistic about the composition of sentences and their parts that discuss the ins and outs of discourse, sentences, clauses and phrases. The problem in this research is how are language errors in the syntactic level of sentence field in haluanriau.co news? the purpose of study is to find out and describe syntactic language errors in haluanriau.co news. The approach in this study is a qualitative approarch. The data in this study is in the form of sentences that are identified as having language errors in sentence fields. The data collection technique, reading technique, note technique and conclusion tecgnique. The data analysis technique is a theory (Miles, 1984) based on the results of this study, it can be conclude that there are 58 errors. Language errors at syntactic level in the sentence area have 12 errors, but the author only examined three errors because the author only evamined the most frequently found errors. 1) sentences without subjects dan without predicates (stuff sentences) with 27 error data 2)the use of foreign terms as many as 21 data errors 3) the use of question words is error data.